A 3D Searchable Database of Transgenic Zebrafish Gal4 and Cre Lines for Functional Neuroanatomy Studies - Marquart, Gregory D.; Tabor, Kathryn M.; Brown, Mary; Strykowski, Jennifer L.; Varshney, Gaurav K.; LaFave, Matthew C.; Mueller, Thomas; Burgess, Shawn M.; Higashijima, Shin-ichi; Burgess, Harold A. (Frontiers in Neural Circuits, 2015)
Transgenic methods enable the selective manipulation of neurons for functional mapping of neuronal circuits. Using confocal microscopy, we have imaged the cellular-level expression of 109 transgenic lines in live 6 day post fertilization larvae, including 80 Gal4 enhancer trap lines, 9 Cre enhancer trap lines and 20 transgenic lines that express fluorescent proteins in defined gene-specific patterns. Image stacks were acquired at single micron resolution, together with a broadly expressed neural marker, which we used to align enhancer trap reporter patterns into a common 3-dimensional reference space. To facilitate use of this resource, we have written software that enables searching for transgenic lines that label cells within a selectable 3-dimensional region of interest or neuroanatomical area. Many of the imaged enhancer trap lines show intrinsic brain-specific expression. However, to increase the utility of lines that also drive expression in non-neuronal tissue we have designed a novel UAS reporter, that suppresses expression in heart, muscle and skin through the incorporation of microRNA binding sites in a synthetic 3' untranslated region. Finally, we mapped the site of transgene integration, thus providing molecular identification of the expression pattern for most lines. Cumulatively, this library of enhancer trap lines provides genetic access to 70 % of the larval brain and is therefore a powerful and broadly accessible tool for the dissection of neural circuits in larval zebrafish.